Gastric Antral Vascular Ectasia - a Rare Cause of Massive Gastrointestinal Bleeding in a Healthy Child, Managed by Argon Plasma Coagulation (Bangladesh Journal of Child Health, 2025)
Upper gastrointestinal (UGI) bleeding in the form of massive hematemesis and melena in children is mostly due to variceal causes or peptic ulcer disease. Vascular angiodysplasia (AD) is a rare etiology of hematemesis and melena in children. Commonly Gastrointestinal angiodysplasia can be encountered secondary to liver cirrhosis and vascular inflammatory disease. Here we report a case of a 3-year-old previously healthy boy without any underlying pathology who presented with hematemesis and melena due to gastric vascular antral ectasia diagnosed by Esophagogastroduodenoscopy (EGD) and managed by argon plasma coagulation (APC). He was discharged for 3 days post-procedure with the recovery of Hb level and remitted tarry stool. No re-bleeding has been documented after that. Vascular AD can be an etiology of gastrointestinal bleeding in children even without cirrhosis. APC is an effective and safe therapy for symptomatic AD in children.BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 182-185